2022
DOI: 10.3390/pharmaceutics14030670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregabalin Combined with Duloxetine and Tramadol on Allodynia in Chronic Postischemic Pain and Spinal Nerve Ligation Mouse Models

Abstract: Although there are various drugs for Neuropathic pain (NP), the effects of single drugs are often not very satisfactory. The analgesic effects of different combinations of pregabalin, duloxetine, and tramadol or the combination of all three are still unclear. Mixtures of two or three drugs at low and high concentrations (7.5, 10, 15, and 20 mg/kg pregabalin; 7.5, 10, 15, and 30 mg/kg duloxetine; 5 and 10 mg/kg tramadol) were administered to chronic postischemic pain (CPIP) and spinal nerve ligation (SNL) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…This is a rather expected result, because previous works have found that duloxetine alone downregulates increased levels of GFAP found in the spinal cord of mice with diabetic neuropathy [29]. Similarly, duloxetine in combination with pregabalin and/or tramadol also decreases GFAP levels in the spinal cord of mouse with chronic postischemic and spinal nerve ligation neuropathy [59]. Interestingly, simvastatin had been found to prevent overexpression of GFAP in the partial sciatic nerve injury mouse model of neuropathy [60], although a reversing (curative) effect was not addressed in that study.…”
Section: Discussionsupporting
confidence: 62%
“…This is a rather expected result, because previous works have found that duloxetine alone downregulates increased levels of GFAP found in the spinal cord of mice with diabetic neuropathy [29]. Similarly, duloxetine in combination with pregabalin and/or tramadol also decreases GFAP levels in the spinal cord of mouse with chronic postischemic and spinal nerve ligation neuropathy [59]. Interestingly, simvastatin had been found to prevent overexpression of GFAP in the partial sciatic nerve injury mouse model of neuropathy [60], although a reversing (curative) effect was not addressed in that study.…”
Section: Discussionsupporting
confidence: 62%
“…During NP, inflammatory cytokine levels increase, leading to the activation of glial cells, particularly microglia and astrocytes in the spinal cord and brain. After astrocyte activation, GFAP expression increases; then, activated astrocytes release inflammatory stimuli such as cytokines and neurotrophic factors to alter the polarization of afferent neurons, and the activation of pain transmission pathways leads to central sensitization [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines released by activated astrocytes play an important role in the development of NP after peripheral nerve injury [38,39]. Nerve injury or inflammation causes the activation of astrocytes in the dorsal horn of the spinal cord and satellite glial cells in the DRG, which regulates the release of pro-inflammatory cytokines, thereby increasing the excitability of neurons, and ultimately triggering pain and its maintenance [23,40]. In our study, the lowest dose of SKI306X we used was 25 mg/kg; at this dose, SKI306X exerted an antiallodynic effect, and 100 mg/kg SKI306X significantly reduced the expression of GFAP in the spinal cord and DRG.…”
Section: Discussionmentioning
confidence: 99%